L'evoluzione delle Stazioni Totali: quarant'anni di innovazione Topcon (GEOmedia, 2018)
A 40-year history, from the introduction of the first total station model, so named because it introduced an absolute innovation compared to the combination theodolite-EDM, up to the last generations of robotic instrumentation for which the involvement of operator is reduced to the minimum terms.A long and unstoppable series of innovations, from recording on memory cards to the first motorized models; from the operating system embedded to the reflectorless measurement, up to the introduction of the images and the "Capture Reality” concept and the combined laser scanning measurement, a real revolution in the world of surveying instrumentation.What will be the next frontier?